Stress Kerja dan Motivasi Kerja pada Petugas Lembaga Permasyarakatan - Dwi Rizkiyani; Susanti R. Saragih (Jurnal Manajemen Maranatha, 2012)
The objective of this research is to examine the effect of work stress on performance, motivation on performance, and work stress and motivation on performance. The research was conducted at Lembaga Pemasyarakatan Klas IIA Anak Pria Tangerang with total sample of 97 correctional officers. The results showed that: (1) Work stress negatively effect work performance of correctional officer and not significant. This result supported by correlation test which r value is -0.011, with b’s value = -0.027 and R square = 0.00019. (2) Work motivation positively effect on work performance of correctional officer which r value of 0.359, with b’s value = 0.655 and R square = 0.129. Finally researcher provides the important managerial implications useful for correctional officer related to work stress, motivation, and performance that will lead to work performance of correctional officer.